Evaluation of the impact of scarcity of water in the Bushbuckridge Local Municipality in Mpumalanga Province : a case study of Islington and Clare villages - Maluleke, Timothy Ellon (University of Limpopo (Turfloop Campus), 2011)
The legacy of apartheid has left the Democratic South African government with many challenges. Sixteen years of governance have not been enough for the state to close the gap between the rich and the poor. Instead, the gap is widening day by day. The Black Economic Empowerment (BEE), the Broad Based Black Economic Empowerment (BBBEE) and other government intervention strategies have not done enough to uplift the standard of living of the majority of people in the country. The poor, living in rural areas, remain the most hard-hit and recipients of the bitter fruits of the past. Little or no development has been taking place in their communities. Regardless of the many efforts by the current government, water supply and sanitation in rural areas are a nightmare. The study was conducted in two rural villages in Bushbuckridge Local Municipality (BLM), namely, Clare B and Islington. In some parts of the villages residents have never fetched water in their streets less than one kilometre for close to a year. The results show that villagers are negatively affected by the lack of water in their communities. The economic power of these communities is very low, most of them are living below the poverty line. The results suggest, as elsewhere, that the BLM should install water pipes that will transfer water from the Injaka Dam to all rural areas in the municipality, as the two villages under study are not the only ones experiencing water shortages in the area.
Thesis (M.Dev.) -- University of Limpopo, 2011
Keywords: Poverty; Water scarcity; Apartheid legacy; Water conservation; Water rights; Water-supply, rural -- South Africa -- Mpumalanga